The Impact of Female Empowerment in Advertising (Femvertising) - Drake, Victoria Elizabeth (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
In recent years, there has been an influx of marketing campaigns that feature female empowerment messaging (“Femvertising”), such as Dove’s “Real Beauty” campaign. While these advertisements are commonly discussed in the media, there is little research evaluating the effectiveness of Femvertising from a marketing perspective. In an online study using a between-subjects experimental design, female participants were randomly exposed to either a traditional television advertisement or Femvertising advertisement for the same brand, and then completed a questionnaire. The analysis found that Femvertising has a positive impact on ad and brand opinions, purchase intentions, and emotional connection to brands.